BMI and TLC increase Neoadjuvant Chemotherapy Response in Patients with Locally Advanced Breast Cancer - Sasongko Hadi Priyono; Oscar Tri Joko Putra; Alfi Yasmina; Hery Poerwosusanta; Eka Yudha Rahman; Ika Kustiyah Oktaviyanti (Faculty of Medicine, Universitas Padjadjaran, 2022)
Anthracycline-based neoadjuvant chemotherapy is the recommended therapy for locally advanced breast cancer (LABC) patients. Unfortunately, no study has reported the relationship between body mass index (BMI), total lymphocyte count (TLC), and responses to this type of chemotherapy. This study aimed to determine the relationship between BMI, TLC, and response to doxorubicin/epirubicin neoadjuvant chemotherapy in LABC patients. A retrospective cohort design was applied to medical records of LABC patients undergoing neoadjuvant chemotherapy at Ulin General Hospital Banjarmasin, Indonesia, from July to December 2021. BMI and TLC data were assessed based on the values before chemotherapy, while the chemotherapy response was measured using the RECIST 1.1 criteria after 3 cycles. Multinomial logistic regression test with 95% confidence level was used to analyze these data. The results showed that as many as 71% of patients experienced a Partial Response (PR), while 5% and 23% of the patients demonstrated Stable Disease (SD) and Progressive Disease (PD), respectively. Each increase in BMI of 1 kg/m2 was significantly associated with an increase in the occurrence of PR and PD by 1.26 times and 1.29 times, respectively, when compared to the occurrence of PD. Meanwhile, an increase in TLC of 100 cells/mm3 was associated with an increase in the occurrence of PR by 6.83 times and an increase in the occurrence of SD. of 6.94 when compared to the occurrence of PD. Therefore, there is a significant relationship between BMI, TLC, and response to anthracycline-based neoadjuvant chemotherapy in LABC patients